Developmental GABA polarity switch and neuronal plasticity in Bioengineered Neuronal Organoids - Maria-Patapia Zafeiriou (Nature Portfolio, 2020)
Brain organoids are important tools to study early development and disease but little is known of their network activity and plasticity. Here the authors generate iPSC-derived neuronal organoids that display early network formation and maturation with evidence for a GABA polarity switch and long-term potentiation.